Refusing the favor : the Spanish-Mexican women of Santa Fe, 1820-1880 - González, Deena J., 1952- (Oxford University Press, 1999)
Refusing the Favor tells the little-known story of the Spanish-Mexican women who saw their homeland become part of New Mexico. A corrective to traditional narratives of the period, it carefully and lucidly documents the effects of colonization, looking closely at how the women lived both before and after the United States took control of the region. Focusing on Santa Fe, which was long one of the largest cities west of the Mississippi, Deena Gonzalez demonstrates that women's responses to the conquest were remarkably diverse and that their efforts to preserve their culture were complex and long-lasting. Drawing on a range of sources, from newspapers to wills, deeds, and court records, Gonzalez shows that the change to U.S. territorial status did little to enrich or empower the Spanish-Mexican inhabitants. The vast majority, in fact, found themselves quickly impoverished, and this trend toward low-paid labor, particularly for women, continues even today. Gonzalez both examines the long-term consequences of colonization and draws illuminating parallels with the experiences of other minorities.; Refusing the Favor also describes how and why Spanish-Mexican women have remained invisible in the histories of the region for so long. It avoids casting the story as simply "bad" Euro-American migrants and "good" local people by emphasizing the concrete details of how women lived. It covers every aspect of their experience, from their roles as businesswomen to the effects of intermarriage, and it provides an essential key to the history of New Mexico. Anyone with an interest in Western history, gender studies, Chicano/a studies, or the history of borderlands and colonization will find the book an invaluable resource and guide.